2021
DOI: 10.3390/biom11050761
|View full text |Cite
|
Sign up to set email alerts
|

Potent Antimicrobial and Antibiofilm Activities of Feleucin-K3 Analogs Modified by α-(4-Pentenyl)-Ala against Multidrug-Resistant Bacteria

Abstract: The dramatic increase in antimicrobial resistance (AMR) highlights an urgent need to develop new antimicrobial therapies. Thus, antimicrobial peptides (AMPs) have emerged as promising novel antibiotic alternatives. Feleucin-K3 is an amphiphilic α-helical nonapeptide that has powerful antimicrobial activity. In our previous study, it was found that the fourth residue of Feleucin-K3 is important for antimicrobial activity. After α-(4-pentenyl)-Ala was introduced into this position, both the antimicrobial activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…It is likely that d -amino acids cannot be recognized by proteases in mammals and that alanine replacement changed the steric hindrance and improved the hydrophobicity of the peptide 33 , 34 , 36 , 37 , 38 , 39 , 40 . Studies have shown that the introduction of α -(4-pentenyl)-Ala into peptide Feleucin-K3 improved its antimicrobial activity and stability 41 , 42 . Based on the aforementioned findings, unnatural hydrophobic alanine ( α -(4-pentenyl)-Ala and d -Ala) was selected to replace residues Asn3 and Asn4 of DR8.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that d -amino acids cannot be recognized by proteases in mammals and that alanine replacement changed the steric hindrance and improved the hydrophobicity of the peptide 33 , 34 , 36 , 37 , 38 , 39 , 40 . Studies have shown that the introduction of α -(4-pentenyl)-Ala into peptide Feleucin-K3 improved its antimicrobial activity and stability 41 , 42 . Based on the aforementioned findings, unnatural hydrophobic alanine ( α -(4-pentenyl)-Ala and d -Ala) was selected to replace residues Asn3 and Asn4 of DR8.…”
Section: Discussionmentioning
confidence: 99%
“…MIC determination method was as previously described . During the 20 d of induction, the sub-MIC concentration of bacteria suspension was cultured to measure the MIC repeatedly.…”
Section: Methodsmentioning
confidence: 99%
“…MIC determination method was as previously described. 12 During the 20 d of induction, the sub-MIC concentration of bacteria suspension was cultured to measure the MIC repeatedly. The development of bacterial resistance was defined as a more than fourfold increase in MICs compared to the initial MICs.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] However, they have conspicuous limitations such as quick renal clearance, poor stability and strong immunogenicity during their use, thus requiring frequent administrations to achieve therapeutic effects, which in turn increases the chance of dramatically oscillating concentrations in blood and adverse effects as well as poor patient compliance. 1,5,6 Many strategies, such as dissolving in appropriate buffers, 7 loading in nanocarriers, [8][9][10] site-specic mutation, 11,12 immobilization in functional materials, 13 modication with polymers, 14,15 etc., can effectively improve the stability and drug delivery. Covalent conjugation of poly(ethylene glycol) (PEG) on the surface of protein therapeutics, named PEGylation, is a type of important strategy to extend the half-life of biomolecules.…”
mentioning
confidence: 99%